2016
DOI: 10.1159/000447806
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase (ASM) is a Negative Regulator of Regulatory T Cell (Treg) Development

Abstract: Background/Aims: Regulatory T cell (Treg) is required for the maintenance of tolerance to various tissue antigens and to protect the host from autoimmune disorders. However, Treg may, indirectly, support cancer progression and bacterial infections. Therefore, a balance of Treg function is pivotal for adequate immune responses. Acid sphingomyelinase (ASM) is a rate limiting enzyme involved in the production of ceramide by breaking down sphingomyelin. Previous studies in T-cells have suggested that ASM is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…CD4+CD25+Foxp3 Tregs, which constitute 5%-10% of peripheral CD4+ T cells, were considered to play a central role in inducing and maintaining tolerance by suppressing T-cell responses in several animal models and in a clinical trial of transplantation [23,24]. The therapeutic potential of Tregs, termed cellular immunotherapy, has been shown to be effective for controlling immune responses in the graft-versus-host disease.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+CD25+Foxp3 Tregs, which constitute 5%-10% of peripheral CD4+ T cells, were considered to play a central role in inducing and maintaining tolerance by suppressing T-cell responses in several animal models and in a clinical trial of transplantation [23,24]. The therapeutic potential of Tregs, termed cellular immunotherapy, has been shown to be effective for controlling immune responses in the graft-versus-host disease.…”
Section: Discussionmentioning
confidence: 99%
“…They also harbor a receptor protein, cytotoxic T-lymphocyteassociated protein 4 (CTLA-4), latently expressing TGF-β on the membrane surface [11]. Although a large number of signaling pathways participate in the regulation of Treg cells [12][13][14][15], forkhead box protein 3 (Foxp3) as Treg specific transcription factor is the most important one. Diminished expression of Foxp3 in CD4 + CD25 + Treg cells created dysfunction of Treg cells in SLE [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Asm-deficiency or Asm-inhibition has been linked to increased T reg frequencies in naïve mice [43, 44]. Here, we studied immunized mice and did not detect any differences in T reg cell number in lymph nodes of immunized Smpd1 -/- mice compared to immunized wild-type littermates (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Our study also included the analysis of regulatory T cells, whose frequency was not altered in Asm-deficient mice after immunization. Hollmann et al and Zhou et al have previously reported an increase of regulatory T cells upon Asm-deficiency in untreated mice [43, 44]. Zhou et al identified ASM as a negative regulator of T reg development, but also noted opposing effects based on the composition of the cytokine cocktail used for experimental T reg induction in their own and in another study by Kue et al [44, 49].…”
Section: Discussionmentioning
confidence: 99%